Cost analysis of colorectal cancer chemotherapy treatment in public and privste healthcare sectors in South Africa - Herbst, Candice-Lee (My University, 2017)
Low-middle income countries are experiencing greater increases in cancer incidence due to changes in lifestyle. Colorectal cancer is one cancer that reflects this increase [1, 2]. As cancer incidence increases so do the costs associated with treatment. Although chemotherapy is not the only cost contributor, it increases costs considerably. This problem is not unique to lowmiddle income countries and requires further research [3]. Therefore this research was conducted to ascertain the cost of colorectal cancer chemotherapy in South Africa for both public and private healthcare sectors and to determine if treatment is equitable between the sectors. Clinical pathways were developed and compared to clinical practice by conducting a retrospective drug utilisation review to determine any variation from the pathways. A costing model was developed to include chemotherapy, supportive medicines, administration fees and administrative fees. The cost was calculated for the developed pathways and the retrospective drug utilisation review allowed for comparison between the sectors and with expected costs. Observations indicate private sector treatments are similar to international standards due to the availability of biological agents however public sector patients have limited access to newer therapies. Comparing the two sectors indicates a higher cost of chemotherapy in the private sector and one such example is the cost difference observed for a commonly prescribed regimen CAPOX for advanced CRC. The observed cost per cycle was R 6 068,28 (public sector) vs. R 9 480,93 (private sector). This is largely due to different access as well as acquisition costs. Nevertheless these patients do have access to newer biological agents. In conclusion, South Africa’s two healthcare sectors differ in access to treatment with the public sector per capita cost for therapy being lower.
Keywords: Chemotherapy; Colorectal Neoplasms